Políticas de la materia y residuos sólidos: descentralización y sistemas integrados - Harvey, Penelope (2012)
This article and the previous «Convergence and divergence between the local and regional state around solid waste management. An unresolved problem in the Sacred Valley» from Teresa Tupayachi are published as complementary accounts on the management of solid waste in the Vilcanota Valley in Cusco. Penelope Harvey and Teresa Tupayachi worked together on this theme. The present article explores how discontinuities across diverse instances of the state are experienced and understood. Drawing from an ethnographic study of the Vilcanota Valley in Cusco, the article looks at the material politics of waste disposal in neoliberal times. Faced with the problem of how to dispose of solid waste, people from Cusco experience a lack of institutional responsibility and call for a stronger state presence. The article describes the efforts by technical experts to design integrated waste management systems that maximise the potential for re-cycling, minimise toxic contamination, and turn ‘rubbish’ into the altogether more economically lively category of ‘solid waste’. However while the financialization of waste might appear to offer an indisputable public good, efforts to instigate a viable waste disposal business in a decentralizing political space elicit deep social tensions and contradictions. The social discontinuities that decentralization supports disrupt ambitions for integrated solutions as local actors resist top-down models and look not just for alternative solutions, but alternative ways of framing the problem of urban waste, and by extension their relationship to the state.